Ekonomskoistorijsko istraživanje Mije Mirkovića o uzrocima ekonomskog zaostajanja Jugoslavije početkom 20. veka - Đurović, Smiljana (Array, 1990)
The author reviews the works of Mijo Mirković and analyzes his views on the economic development of the Yugoslav lands as compared to other European countries. Special attention is given to Mirković's doctoral thesis "The Main Causes of Low Economic Efficiency in Slavs" and to his book "Industrial Policy" published in Belgrade in 1937